PREVENTIVE MAINTENANCE OF TURBINES IN UNIT 3 AT PT. PLN INDONESIA POWER BANTEN 3 POMU LONTAR - Intifalda, Tegar; Dwinanto, Dwinanto; Caturwati, Ni Ketut; Satria, Dhimas; Listijorini, Erny; Rosyadi, Imron (Trends in Mechanical Engineering Research, 2024)
Maintenance on the turbine must always be carried out, because if one component of the turbine engine is damaged, it will affect the entire performance of the turbine engine. The function of bearing lubrication in turbines is to prevent direct contact between the bearing and the turbine shaft. Therefore, lubrication is needed. Bearing lubrication on the turbine is a very important issue so that the turbine should not be rotated without lubrication will cause material damage. Preventive maintenance of turbines can be pursued by implementing QCC PM. Adding a portable purifier when excessive water content occurs, adjusting the pressure steam seal serves to prevent main steam from entering the bearing area which can cause high water content due to mixing of oil with water. Making a steam block serves to prevent steam from entering the bearing area lubricated by VG 46 medium oil, causing high water content. And routine maintenance to check the mesh aims to assess the feasibility of the mesh and the suitability of the needs of the cleanliness purifier oil system which can be seen from the CBM data, namely tribology monitoring.